PWE-062 The outcomes and benefits of moving stable inflammatory bowel disease patients from a paper based self management system to an supported, self help and management programme (ibd-sshamp) with specialist overview. (22nd June 2015) - Price, T; Lithgo, K; Johnson, MW
Abstract : Introduction: Self management in inflammatory bowel disease (IBD) has proven itself to be a safe and cost effective method of managing the more stable IBD patients. It is however not without its issues. In February 2012 we introduced our IBD-Supported, Self Help and Management Programme (IBD-SSHAMP) with specialist nursing and consultant support to try an avoid some of the issues inherent on relying on self management alone. We now have 3 years experience in running IBD-SSHAMP with regular virtual telephone clinics and personalised web-site supported management. Some of the outcomes seen in transferring patients from self management to a supported self management system are presented here. Method: In total 425 of our more stable IBD patients are now managed in the community on IBD-SSHAMP. Using hospital coding data, Evolve (the hospital–s electronic record system), the National IBD Registry and HICSS (the endoscopy reporting software) we reviewed the following aspects;- number of flares, steroid courses, emergency outpatient clinics, and hospital admissions. By continuing to keep them under a close monitoring system we were interested to know if improvements would be seen in their compliance with prophylactic medication and their uptake on surveillance colonoscopy. Results: In 3 years just 43 flares were experienced in this cohort, and most of these were successfully treated using mesalazines alone. Steroids were however required in 16 of these patients, most of which was directed by telephone consultation. In that 3 year period only 8 required urgent outpatient appointments (OPAs) were required and no patients needed hospital admission. Many patients on pure self management had been lost to follow up and had avoided surveillance colonoscopy. Unfortunately after bringing these patients back into a monitored and supported management system we have subsequently found 3 colorectal cancers (ascending, sigmoid and ano-rectal) within this group. Most of these patients were overdue their surveillance colonoscopy, but despite the known risks 114 still declined surveillance. Other cancers were also found amongst this cohort, including; 2 breast cancers, one prostrate cancer and one skin cancer. Most were happy with the new IBD- SSHAMP, but 3 patients chose to attend standard hospital based OPAs. Conclusion: IBD-SSHAMP has been shown to be a highly efficient and cost effective method of keeping community based IBD patients under close specialist review. Reductions in flares, emergency OPAs and admissions have been seen. It has been well received by the patients who prefer to be supported rather than discharged and left alone to self manage. Disclosure of interest: None Declared.